Predictive factors of trans-arterial chemoembolization (tace) efficacy for hepatocellular carcinoma in arterial phase computed tomographic scan - Mohamed , Dahlia (2017)
The aim of this study was (1) to evaluate demographic factors of patient with hepatocellular carcinoma who underwent TACE procedure (2) to identify the correlation between predictive factors (tumour attenuation, size and site of tumour) and response of tumour (volume of residual viable tumour) to TACE procedure (3) to determine which predictive factor contribute more to better tumor response to TACE. Patients diagnosed with Hepatocellular carcinoma who underwent TACE procedure using drug eluting microparticles as the embolized material recruited from PACS system at Radiology Department Hospital USM and Hospital Selayang. CT findings (pre and post TACE) of 144 tumors were analysed using several parameters (attenuation, size and site of tumour). Response of tumour to TACE was assessed based on reduction of size of tumour volume. A total of 144 nodules of HCC were analysed from pre- and post-TACE CT scan in arterial phase. Simple linear regression analysis revealed that tumour attenuation and size have significant association with the tumour response to TACE (P<0.001). There were no significant association found between the site of tumour [central or peripheral (p=0.453) and right lobe or left lobe (P=0.705)] with tumour response to TACE. Out of the two statistically significant variables, we found that the strongest predictive factor for better TACE response based on multiple linear regression analysis was the tumour size. Smaller tumor and higher tumour attenuation (measured in Hounsfield unit) were the significant predictive factors for better tumour response to TACE. Location of the tumour showed no statistical significant association with better TACE response.